Calculation of the thermal mode of the LED device - Kulik, Natalia; Danchenkov, Jakov (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The problem of heat removal from the substrate of LED light sources is considered. Modern methods of cooling of LEDs are reviewed. The calculation method is given and the radiator area for passive heat removal is calculated. The radiator was selected according to the given criteria.